P-189 Hospices working with commissioners – mutually beneficial or a necessary evil?. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Palin, Heather; Willis, Derek
Abstract : Background: Hospices' value within the third sector is in their specific strategic organisational capabilities. It could be argued that this potential is unrecognised and untapped. The specialist nature of the services that hospices provide and their financial independence and freedom to develop and invest in services place them in a strong position to influence NHS commissioning of services. This study uses the VRIN model to assess the organisation's resources and to demonstrate the hospice's specific strategic capabilities. (Barney & Hesterley, 2010). This study demonstrates how one hospice has successfully challenged commissioning intentions and evidenced a counter proposal which resulted in the funding and delivery of an enhanced Hospice at Home service. Aim: To prove that increased provision of spells of Hospice at Homecare 24/7 would improve care and support the choice to be cared for and die at home and reduce hospital admissions. To demonstrate that patients who fit the criteria for Hospice at Home also fit the criteria for CHC funding and secure that funding for the expansion of service. Method: Through semi-structured interviews we set out to evidence the true gaps in community palliative and end of life care and the approach to commissioning hospice services. Scoping of the views of the below: Phase 1 – Local GPs, community nurses and community. Phase 2 – Commissioners from 2 CCGs Phase 3 – Wider group of hospice directors (Survey Monkey) Results: Counter proposal accepted Joint funding of Proof of Concept Increased numbers of patients supported at home. Hospital admissions avoided Engagement of CHC and funding agreed. Conclusion: This study demonstrates the potential of hospice strategic organisational capabilities and the value of good relationships with commissioners that place hospices as equal, influential partners within a struggling economic and healthcare environment. This study demonstrates how one hospice has successfully challenged commissioning intentions and evidenced a counter proposal resulting in the funding and delivery of an enhanced Hospice at Home service.